Role of Mother Tinctures (Homoeopathy for All, 2024)
Mother Tincture is the concentrated  herbal extract made from raw lant  materials (like roots, leaves or  flowers) and alcohol and water which  serves as a base. It is the foundational  substance used in homoeopathy  to created diluted remedies.in  homoeopathy mother tincture is  made by soaking or macerating plant  or other sources in alcohol, which  extracts the active compounds. This  base is extract is then diluted in a  series of step to make homoeopathic  remedies. Mother tinctures serve as  the initial, concentrated form of a  remedy from which further dilutions  and preparations are made.
Keywords: RAW MATERIAL; diluted